0775 Do Markers of Obstructive Sleep Apnea Severity Predict Attention Problems In Children?. (27th April 2018) - Dhaliwal, S; Lewin, D; Huntley, E
Abstract: Introduction: Sleep disordered breathing in children has been linked to attention concerns. Left untreated, OSA may give rise to the clinical diagnosis of Attentional Deficit Hyperactivity Disorder and contribute to other behavior problems. The aims of the current project were to test whether (a) severity of OSA predicted greater ADHD symptom scores and clinical diagnosis, and (b) markers of OSA severity were differentially related to clinically significant externalizing behavioral disorders. Methods: In a prospective study, the parents of 71 children with OSA and 35 without (53% female, mean age = 7.9 years; SD = 1.4 years) completed the Child Behavioral Checklist (CBCL), yielding scaled scores in domains of attention and behavior problems. Children also underwent a one-night polysomnography study. OSA severity was determined by obstructive apnea hypopnea index (1< AHI ≤5 mild, 5< AHI ≤10 moderate, AHI >10/hr severe). Linear regressions adjusted for age, body mass index (BMI), race, and parental education. Results: OSA severity was related to lower parental education, African American race, and body mass index (ps<.05). OSA severity exhibited a dose-response positive association with attention problems, at each severity level above mild (β=4.36, p=.02 for moderate; β=9.93, p<.001 for severe). OSA severity also predicted ADHD diagnostic thresholds (β=3.53, p<.05 for moderate; β=5.99, p<.01 for severe OSA). Between-group analyses indicated that children with OSA also experienced greater general externalizing behaviors, as well as greater conduct problems (ps<.05), and trended toward greater oppositional defiance (p=.076). Conclusion: OSA severity is linked to both attention difficulties and clinical thresholds of ADHD. Children with OSA exhibited increased symptoms of externalizing, conduct and oppositional behavioral problems. Future work shared neural mechanisms and improved diagnosis of co-morbid OSA, behavior and attention problems. Support (If Any):